2004
DOI: 10.1016/j.ymthe.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Novel mouse model for carcinoembryonic antigen-based therapy

Abstract: Many novel cancer therapies, including immunotherapy and gene therapy, are specifically targeted to tumor-associated molecules, among which carcinoembryonic antigen (CEA) represents a popular example. Discrepancies between preclinical experimental data in animal models and clinical outcome in terms of therapeutic response and toxicity, however, often arise. Preclinical testing can be compromised by the lack of CEA and other closely related human CEA family members in rodents, which lack analogous genes for mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 37 publications
7
89
0
Order By: Relevance
“…1H), we observed increased intensity and distribution of CEACAM6 immunoreactivity in the hyperplastic alveolar epithelium that develops in response to injury, whereas, in adult lung, CEACAM6 is expressed in only a subpopulation of type II cells. It is possible that CEACAM6, via its antiapoptotic activity for lung epithelial cells (24), promotes cell proliferation in response to lung injury, while also contributing to innate immune defense, along with other lung proteins, such as SP-A and SP-D. Our laboratory is currently examining CEACAM6 expression in additional sections of injured infant lung and in bleomycin-injured lungs of transgenic mice expressing human CEACAM6 (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1H), we observed increased intensity and distribution of CEACAM6 immunoreactivity in the hyperplastic alveolar epithelium that develops in response to injury, whereas, in adult lung, CEACAM6 is expressed in only a subpopulation of type II cells. It is possible that CEACAM6, via its antiapoptotic activity for lung epithelial cells (24), promotes cell proliferation in response to lung injury, while also contributing to innate immune defense, along with other lung proteins, such as SP-A and SP-D. Our laboratory is currently examining CEACAM6 expression in additional sections of injured infant lung and in bleomycin-injured lungs of transgenic mice expressing human CEACAM6 (12).…”
Section: Discussionmentioning
confidence: 99%
“…PCR and agarose gel electrophoresis was performed on 70 ng of cDNA from each sample, plus a no cDNA control (21, 25, 29 cycles) using an annealing temperature of 55°C in a PT-200 Peltier Thermal Cycler (MJ Research, Waltham, MA). Primer sequences used are specific for human CEACAM6 (12) with an expected product of 353 bp: 5= primer Ï­ 5=-TACTCAGCGTCAAAAGGAAC-3= and 3= primer Ï­ 5=-AGAGACTGTGATCATCGTGA-3=.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also suggested that CEACAM1 and CEACAM6 also play a significant role in colonic tumor development (Neumaier et al, 1993;Nollau et al, 1997a, b;Scholzel et al, 2000;Jantscheff et al, 2003). As the mouse neither expresses CEA nor CEACAM6 and relies for most of its CEA-related functions on the expression of CEACAM1, studies investigating the role of these proteins depend on the generation of adequate transgenic mouse models (Chan and Stanners, 2004) or the availability of mice deficient for CEACAM1. In this manuscript, we describe the generation of the Ceacam1À/À mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CEACAM1 is widely expressed on lymphocytes, and CEACAM1-induced signaling can influence immune cell activation (28)(29)(30)(31)(32)(33)(34)(35), potentially providing a mechanism for immune evasion by N. gonorrhoeae. While no study to date has looked at CEACAM expression within the male urethra, a transgenic mouse line expressing human CEACAMs in a manner that closely reflects the spatiotemporal expression pattern in humans expresses CEACAM5 on the urethral mucosal surface (36).…”
mentioning
confidence: 99%